(3YeGdbI GdESdGe (B/s - (3GHQGgje, YHO GdbGOQ GdTjNs ((3MdH, ShQjG (B:s (3OGQ Gdbde GdYQHj ddWHGYI hGdfTQ hGdJhRjY,s, 1999)
(3gPG GdcJGH jMhj YOO ef GdTNUjGJ GdESdGejI GdYXjeI GdJj dYHJ OhQG cHjQG haYGdG, hcGf dgG GdOhQ GdQGFO hGdCKQ GdYXje aj bjGOI GdaJhMGJ GdcKjQI YHQ GdJGQjN GdESdGej, hgPG GdcJGH jJMOK Yf TNUjJjf hgeG NGdO Hf GdhdjO hCHh YHjOI Hf GdLQGM(B.s
(3GdeMJhjGJ (B: (3eL(B. 1. (3NGdO Hf GdhdjO(B-(3CHh YHjOI Hf GdLQGM(B-(3eL(B. 2. (3SYO Hf CHj hbGU(B-(3GdeKfj Hf MGQKI hYdj Hf GdMSjf(B-(3eL(B. 4. (3YHO GdQMef Hf Yha(B-(3GdfYeGf Hf ebQf(B-(3eL(B. 5. (3CHh PQ GdZaGQj(B-(3SYO Hf eYGP(B-(3eL(B. 6. (3YeQ Hf GdYRjR(B-(3GdMLGL Hf jhSa(B-(3eL(B. 7. (3GdMSf hGdMSjf(B.s
Keywords: (3GdUMGHI hGdJGHYhfs -- (3JQGLes